Consensus statement on insulin therapy in chronic kidney disease. (May 2017) - Rajput, Rajesh; Sinha, Binayak; Majumdar, Sujoy; Shunmugavelu, M.; Bajaj, Sarita
Highlights: Insulin doses in CKD to be reduced with lower eGFR levels. Insulin doses in CKD can be estimated according to body weight. The optimal glycaemic target should also be determined as per the GFR value. Blood glucose monitoring should be done as per the severity of kidney disease. SMBG should be the preferred choice, however, CGMS may be considered if patients can afford. Abstract: Introduction: Diabetes mellitus (DM) is one of the leading causes of chronic kidney disease (CKD) which eventually leads to insulin resistance and decreased insulin degradation. In patients with diabetic kidney disease (DKD), the overall insulin requirement declines which necessitates the reassessment for individualization, adjustment and titration of insulin doses depending on the severity of kidney disease. Objective: To provide simple and easily implementable guidelines to primary care physicians on appropriate insulin dosing and titration of various insulin regimens in patients with DKD. Methods: Each insulin regimen (basal, prandial, premix and basal-bolus) was presented and evaluated for dosing and titration based on data from approved medical literatures on chronic kidney disease. These evaluations were then factored into the national context based on the expert committee representatives' and key opinion leaders' clinical experience and common therapeutic practices followed in India. Results: Recommendations based on dosing and titration of insulins has been developed. Moreover, the consensus group also recommended the strategy for dose estimation of insulin, optimal glycaemic targets and self-monitoring in patients with DKD. Conclusion: The consensus based recommendations will be a useful reference tool for health care practitioners to initiate, optimise and intensify insulin therapy in patients with DKD.